A description of the prevention practice Dengue Hemorrhagic Fever (DHF) in endemic areas - Ernawati Ernawati; Cicilia Nony; Siska Evi Martina (University of Muhammadiyah Malang, 2018)
Dengue Hemorragic Fever (DHF) is a disease that spread rapidly. The way of spreading dengue fever through Aedes Aegypti mosquito bites. During the year of 2005-2009, the incident of DHF in DKI Jakarta was always high. It is a challenge for local government in Jakarta to solve the problem. Controling the growth of dengue virus through PSN (Pemberantasan Sarang Nyamuk) movement requires perseverance, motivation, and community participation. Therefore, research which describe about health behavior related practice of DHF prevention in society is need to be conducted. This quantitative research with cross sectional method aim to describe the DHF prevention practice in an endemic DHF place. The purposive sampling method was used to gain 148 research participants. This study found that 68,69% research participants have prevention practices at a moderate level, and there are still 15% have bad prevention practices. Based on this it is expected that assistance and support of health workers can improve the prevention practice of DHF.